Holocene infill of the Anglesea Estuary, Victoria: a keep-up estuary in a geologically constrained environment. Issue 6 (18th August 2021) - Kennedy, D. M.; Wong, V. N. L.; Jacobsen, G. E.
Abstract: Holocene coastal infill was examined in Anglesea Estuary, an intermittently open barrier-type estuary in Victoria. Based on coring and radiocarbon dating, it was found that accommodation space in the estuary was almost entirely occupied in the early–mid Holocene corresponding to periods of higher sea-level. The pattern of infill is in stark contrast to established models of estuarine sedimentation developed on the east Australian coast. The contemporary estuary is composed of two distinct sedimentary basins. The upper basin is infilled by autochthonous peaty-marsh sediments, whereas the lower basin is infilled by saltmarsh material. The traditional tripartite flood-tide delta–central mud basin–fluvial delta sequence is absent. The contemporary estuary appears to have evolved as two distinct basins, which are connected through hydrodynamic rather than sedimentological processes. This pattern of connected basins occurs from the top of the catchment to the wave base, with the contemporary estuary infilling the two basins coincident with modern sea-level. Low sediment supply from both terrestrial and marine sources and bedrock-limited accommodation space means that Anglesea can be considered to be geologically constrained barrier estuary. KEY POINTS: Geological-control limits mud basin development. Low allochthonous sediment supply significantly affected estuarine facies in Anglesea. Anglesea Estuary infilled to higher mean sea-level elevations in the mid Holocene. Anglesea Estuary is composed of two distinct sedimentary basins.